New existence results on neutral fractional differential equations in the concept of Atangana-Baleanu derivative with impulsive conditions - et. al., U.Karthik Raja, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In this article, We study an existence and uniqueness of solutions for an impulsive fractional neutral differential equations via Atangana-Baleanu fractional derivative with dependence on the lipschitz first derivative conditions in Banach space. This results are based on fixed point theorems. An example is given to illustrate the main results.